Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1088/2053-1591/ab99e6
|View full text |Cite
|
Sign up to set email alerts
|

Steam oxidation behavior of Y-bearing cladding tube with aluminizing coating

Abstract: A kind of Y-bearing ferritic/martensitic fuel cladding tube with qualified dimensions, acceptable mechanical properties as well as good flattening and flaring performance was manufactured recently by our group. In this paper, to improve and further evaluate its oxidation resistance, the cladding tube was aluminized firstly and then subjected to high temperature steam oxidation at 1200°C for 8 h. The results indicated that aluminizing coating with gradient content of Al was prepared on the tube successfully. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…According to the mentioned cases, the presence of steam or water vapor in the atmosphere can accelerate the release of Al to the outside and protect the substrate from oxidation by forming Al 2 O 3 . This has been confirmed in several studies [22,23]. This mechanism can be explained by considering the presence of H The cross-sectional image of Al 321 after 100 h of steam oxidation at 700 °C is shown in figure 4(c).…”
Section: Vapor Oxidation Behavior Of the Coatingsupporting
confidence: 73%
“…According to the mentioned cases, the presence of steam or water vapor in the atmosphere can accelerate the release of Al to the outside and protect the substrate from oxidation by forming Al 2 O 3 . This has been confirmed in several studies [22,23]. This mechanism can be explained by considering the presence of H The cross-sectional image of Al 321 after 100 h of steam oxidation at 700 °C is shown in figure 4(c).…”
Section: Vapor Oxidation Behavior Of the Coatingsupporting
confidence: 73%
“…The CTE values of PBIIs range between 43 and 52 ppm K −1 . It is reported that the in‐plane orientation depending on the interchain interaction and linearity is associated to the CTE values 66–68 . 5b‐HPMDA displays a lower CTE value than 5a‐HPMDA, which is accordant to the aforesaid opinion, because 5b with the strong linearity induces PBII backbones to the compact packing and powerful interaction between chains, inhibiting the motions of molecular chain segments.…”
Section: Resultsmentioning
confidence: 60%